New species of eleutherodactylus of colombia (amphibia: leptodactylidae). i: five new species from the paramos of the cordillera central (1980)
Eleutherodactylus obmutescens , E. racemus, and E. simoterus are new species of the unistrigatus Group named from the Páramo de Puracé, Páramo de las Hermosas and Páramo de Letras, respectively, in the Cordillera Central of Colombia. The new species are allied to E. orcesi Lynch and E. thymelensisLynch known from páramos primarily on the Cordillera Occidental of Ecuador. Eleutherodactylus leptolophus and E. peraticus are new species of the unistrigatus Group named from the Páramo de Puracé and Páramo de las Hermosas, respectively. These are diminutive frogs most closely related toE. myersi (Goin and Cochran) from the Nudo de Pasto and to E. trepidotus Lynch from the subpáramos of the eastern versant of the Cordillera Oriental of Ecuador. The five new species with E. buckleyi (Boulenger) comprise the six species of Eleutherodactylus now known to inhabit páramos in the Cordillera Central of Colombia.